Assessment of the Concurrent Validity and Reliability of the Persian Version of the Pediatric Balance Scale in Schoolchildren with Down Syndrome - Maedeh Shahbaz-Borujeni; Rahman Sheikhhoseini; Fariba Mohammadi; Hashem Piri (International journal of school health (Online), 2025)
Background: Individuals with Down Syndrome face numerous challenges related to movement and balance. The present study evaluated the reliability and concurrent validity of the Persian version of the Pediatric Balance Scale in schoolchildren.Methods: In this cross-sectional correlational study, 37 students (23 girls and 14 boys) with Down Syndrome aged 7 to 15 were recruited through convenience sampling technique. The participants were selected from special education schools in the spring of 2024. Initially, the procedure for performing the tests was taught to the children. Then, at a two-week interval (one session per week for a child), the tests were administered by two independent examiners. The Timed Up and Go, Pediatric Balance Scale, and Standing Stork Test were used to assess balance. The statistical tests used in this study were the intra-class correlation coefficient and Pearson’s correlation coefficient, at a 95% confidence level.Results: Pearson’s correlation test revealed a substantial correlation between Pediatric Balance Scale and Standing Stork Test (r=0.585, P<0.001), and an inverse correlation between Pediatric Balance Scale and the Timed Up and Go test (r=-0.606, P<0.001). These correlation coefficients indicated a moderate to strong relationship between these tests and Pediatric Balance Scale. Based on the intra-class correlation coefficients obtained, the within-evaluator (ICC=1.000) and between-evaluator (ICC=0.973) agreements were high and reliable.Conclusions: Pediatric Balance Scale appears to have excellent reliability and appropriate concurrent validity for assessing balance in schoolchildren with Down Syndrome. Therefore, it is recommended that this balance scale be used to evaluate balance in these individuals.